The Eigenwelt of Technoculture - Darmawan, Ruly (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
The discourse on technoculture reflects the relationship between humans and technology. Such a relationship is built upon an understanding that humans need technology to increase efficiency. In fact, technocultural discourse produces a way to see and understand the world from a different angle. Up to today, the technocultural life world remains largely unexplored.